Metaepistemology Realism and Anti-Realism (Palgrave Innovations in Philosophy, 2018)
This book contains twelve chapters by leading and up-and-coming philosophers on metaepistemology, that is, on the nature, existence and authority of epistemic facts. One of the central divides in metaepistemology is between epistemic realists and epistemic anti-realists. Epistemic realists think that epistemic facts (such as the fact that you ought to believe what your evidence supports) exist independently of human judgements and practices, and that they have authority over our judgements and practices. Epistemic anti-realists think that, if epistemic facts exist at all, they are grounded in human judgements and practices, and gain any authority they have from our judgements and practices. This book considers both epistemic realist and anti-realist perspectives, as well as perspectives that "transcend" the realism/anti-realism dichotomy. As such, it constitutes the "state of the art" with regard to metaepistemology, and will shape the debate in years to come.